Fundamental of Entrepreneurship ENT300 : EZ Bowling Centre / Eiman Zulhakim Mohammad - Mohammad, Eiman Zulhakim (2020)
EZ Bowling Centre will be an entertainment centre for all ages of customer can enjoy as individual por in groups. The new computer technology enables anyone to experience the excitement of the sport without having to know how to keep score, because it is done automatically by the computer and displayed on a monitor. EZ Bowling Centre will be located in Naim Paragon Street Mall. There are zero bowling centre in Bintulu and that will make us be the first bowling centre in Bintulu. EZ Bowling Centre marketing strategy is to emphasize in customer service. We will offer a fair fare to allow more customer to enjoy bowling at an affordable price.